2023
DOI: 10.1038/s41377-023-01174-7
|View full text |Cite
|
Sign up to set email alerts
|

Mold-free self-assembled scalable microlens arrays with ultrasmooth surface and record-high resolution

Abstract: Microlens arrays (MLAs) based on the selective wetting have opened new avenues for developing compact and miniaturized imaging and display techniques with ultrahigh resolution beyond the traditional bulky and volumetric optics. However, the selective wetting lenses explored so far have been constrained by the lack of precisely defined pattern for highly controllable wettability contrast, thus limiting the available droplet curvature and numerical aperture, which is a major challenge towards the practical high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Sun [ 72 ] reported that the simple pre-deposition of an ethanol layer enabled a series of procedures, including homogenization, solvent exchange, post-stretching, and air drying, thereby uniformly depositing densely structured graphene nanosheets and effectively limiting and eliminating the coffee-ring effect during inkjet printing, as shown in Figure 7 b. Inkley [ 73 ] successfully used triethylene glycol for pre-wetting the powder bed before printing, significantly expanding the range of droplet spacing to produce continuous lines, as shown in Figure 7 c. Duan [ 74 ] significantly altered the fluid drying kinetics by adding surfactants during solution printing and increasing the contact-line friction between the aqueous solution and the underlying non-wetting organic crystalline film. As a result, centimeter-level highly-arranged arrays of organic crystals were successfully prepared on different substrates, as shown in Figure 7 d. Liu [ 75 ] reacted large-scale droplet arrays with controlled curvature by selectively modifying the surface using tunable oxygen plasma, promoting precise patterns by adjusting chemical contrast; they also used droplet dosage modification to achieve precise adjustment, as shown in Figure 7 e. Feng [ 76 ] proposed and verified an efficient, high-throughput method for the rapid preparation of uniform droplet arrays induced by an electric field in multiple emulsion droplets within micropores. Polydisperse emulsions were prepared through mechanical stirring and then filling them into hydrophobic micropores through screen printing.…”
Section: Control Methods For Droplet Printingmentioning
confidence: 99%
See 2 more Smart Citations
“…Sun [ 72 ] reported that the simple pre-deposition of an ethanol layer enabled a series of procedures, including homogenization, solvent exchange, post-stretching, and air drying, thereby uniformly depositing densely structured graphene nanosheets and effectively limiting and eliminating the coffee-ring effect during inkjet printing, as shown in Figure 7 b. Inkley [ 73 ] successfully used triethylene glycol for pre-wetting the powder bed before printing, significantly expanding the range of droplet spacing to produce continuous lines, as shown in Figure 7 c. Duan [ 74 ] significantly altered the fluid drying kinetics by adding surfactants during solution printing and increasing the contact-line friction between the aqueous solution and the underlying non-wetting organic crystalline film. As a result, centimeter-level highly-arranged arrays of organic crystals were successfully prepared on different substrates, as shown in Figure 7 d. Liu [ 75 ] reacted large-scale droplet arrays with controlled curvature by selectively modifying the surface using tunable oxygen plasma, promoting precise patterns by adjusting chemical contrast; they also used droplet dosage modification to achieve precise adjustment, as shown in Figure 7 e. Feng [ 76 ] proposed and verified an efficient, high-throughput method for the rapid preparation of uniform droplet arrays induced by an electric field in multiple emulsion droplets within micropores. Polydisperse emulsions were prepared through mechanical stirring and then filling them into hydrophobic micropores through screen printing.…”
Section: Control Methods For Droplet Printingmentioning
confidence: 99%
“…( e ) MLA manufacturing process based on selective wetting. Reproduced with permission from [ 75 ] under the Creative Commons CC BY license. ( f ) ECDA chip-manufacturing process schematic: photolithography of micropores on ITO glass coated with Hyflon, emulsion filling, chip assembly and sealing, and micropore-constrained droplet electropolymerization.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Kotz et al demonstrated post-processing an MLA made of twophoton curable silica nanocomposite resin through thermal debinding and sintering to achieve a surface roughness of 6 nm [46]. Liu et al demonstrated a self-assembly-based moldfree approach of mass-production of scalable MLAs, with ultrasmooth surface (roughness of around 0.3 nm), ultrahigh resolution, and large variable curvatures [155]. The second requirement of a high fill factor is to maximize the light collection efficiency.…”
Section: Lens Arrays Compound Lens and Light Field Imagingmentioning
confidence: 99%
“…The generation of multipartite quantum entanglement in the CV regime has attracted great interest due to its enormous potential in various applications and protocols, ranging from quantum communication, [17][18][19][20] to quantum memory, [21,22] and quantum imaging. [23,24] A large number of experimental studies on its generation has been reported. The most well-established technique for generating multipartite CV entanglement is achieved by mixing the individual squeezed states on a linear beam-splitter network.…”
Section: Introductionmentioning
confidence: 99%